Some novel mathematical analysis on the fractional-order 2019-nCoV dynamical model - Owoyemi, Abiodun Ezekiel (Mathematical methods in the applied sciences, 2022)
© 2022 The Authors. Mathematical Methods in the Applied Sciences published by John Wiley & Sons, Ltd.